FATIGUE LIFE BEHAVIOUR OF FIBERGLASS-REINFORCED COMPOSITES SUBJECTED TO UNDERLOADING - Jimit, R.H.; Zakaria, K.A.; Bapokutty, O.; Ali, M.B.; Rivai, A. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
Each Fiberglass-reinforced composites (FGRC) can be used as replacement of most metal in manufacturing vehicle parts due to their excellent mechanical properties, low cost and corrosion resistance. Fatigue failure occurs in FGRC upon subjected to constant amplitude loading (CAL). However, studies on the behaviour of FGRC are still in lacking of tools for predictive engineering and analysis mainly due to inadequate understanding of these materials behaviour including it’s integrity when subjected to variable amplitude loadings (VAL). Therefore, this study aim to investigate the effect of underload towards the fatigue life behaviour of FGRC with different laminate orientations. The Reinforcement materials use is unidirectional fiberglass with [0/90]° and [±45]° orientations and chopped strand mat is choose to study the effect of periodic underload in cycles. Meanwhile polyester resin is use as the matrix material. The FGRC composite is fabricated using a hand lay-up technique according to ASTM D3039 for tensile test and ASTM D3479 for fatigue test. Results showed that underload effect deteriorate the fatigue life behaviour of FGRC from 1.4% to 18% decrement from the actual value when being compared to result in CAL.